Grammatical and Discourse Competence Analysis in Writing Argumentation Paragraph - Linda Aprillianti (IJEE (Indonesian Journal of English Education), 2019)
ABSTRACTWriting is a form of embodiment of indirect communication. It is required to pay attention to the structure associated with the elements of writing so that readers can understand the message conveyed by the writer. This study is intended to identify the grammatical and discourse competence of the students in writing argumentative paragraphs. The research used was qualitative descriptive approach with analytical method. The data of this study were taken from the students’ assignment papers related to writing argumentative paragraph in Komunitas Cerdas Course. There were twenty task sheets resulting from students’ writings. All of this data were analyzed in terms of grammar and discourse.   The data collection techniques used was written tests. In analyzing the data, the writer used the theory of Miles and Huberman, so the form of study was given in short description. The results of the analysis showed that students already had sufficient competence in grammar or discourse, further, in general, the students already had grammatical competence and sufficient discourse competence. However, there were some aspects in grammar that needed to get more attentions, such as  the ability of the students to arrange words into good sentences.ABSTRAKMenulis adalah bentuk perwujudan komunikasi tidak langsung. Hal ini diperlukan untuk memperhatikan struktur yang terkait dengan unsur-unsur penulisan sehingga pembaca dapat memahami pesan yang disampaikan oleh penulis. Penelitian ini dimaksudkan untuk mengidentifikasi kompetensi gramatikal dan wacana siswa dalam menulis paragraf argumentatif. Penelitian ini juga memberikan koreksi kesalahan siswa dalam menulis paragraf argumentatif. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan metode analitik. Data penelitian ini adalah kertas tugas siswa terkait dengan menulis paragraf argumentasi di Kursus Komunitas Cerdas. Ada dua puluh lembar tugas yang merupakan hasil tulisan siswa. Semua data ini dianalisis dalam hal tata bahasa dan wacana. Teknik pengumpulan data yang digunakan adalah tes tertulis. Teknik analisis data, penulis menggunakan teori Miles dan Huberman, sehingga bentuk penelitian diberikan dalam deskripsi singkat. Hasil analisis menunjukkan bahwa siswa sudah memiliki kompetensi yang cukup dalam tata bahasa atau wacana. Berdasarkan hasil analisis, secara umum siswa sudah memiliki kompetensi tata bahasa dan kompetensi wacana yang cukup. Tetapi ada beberapa aspek dalam tata bahasa yang perlu mendapat perhatian lebih, sedangkan kompetensi wacana, kemampuan siswa untuk mengatur kata-kata menjadi kalimat yang baik masih perlu banyak peningkat. How to Cite: Aprillianti,L. (2019). Grammatical and Discourse Competence Analysis in Writing Argumentation Paragraph. IJEE (Indonesian Journal of English Education), 6(2), 133-142. doi:10.15408/ijee.v6i2.11944